High non-photochemical quenching of VPZ transgenic potato plants limits CO2 assimilation under high light conditions and reduces tuber yield under fluctuating light - Lehretz, Günter; Schneider, Anja; Leister, Dario; Sonnewald, Uwe (Journal of integrative plant biology, 2022)
Under natural conditions, photosynthesis has to be adjusted to fluctuating light intensities. Leaves exposed to high light dissipate excess light energy in form of heat at photosystem II (PSII) by a process called non-photochemical quenching (NPQ). Upon fast transition from light to shade, plants lose light energy by a relatively slow relaxation from photoprotection. Combined overexpression of violaxanthin de-epoxidase (VDE), PSII subunit S (PsbS) and zeaxanthin epoxidase (ZEP) in tobacco accelerates relaxation from photoprotection, and increases photosynthetic productivity. In Arabidopsis, expression of the same three genes (VPZ) resulted in a more rapid photoprotection but growth of the transgenic plants was impaired. Here we report on VPZ expressing potato plants grown under various light regimes. Similar to tobacco and Arabidopsis, induction and relaxation of NPQ was accelerated under all growth conditions tested, but did not cause an overall increased photosynthetic rate or growth of transgenic plants. Tuber yield of VPZ expressing plants was unaltered as compared to control plants under constant light conditions and even decreased under fluctuating light conditions. Under control conditions, levels of the phytohormone abscisic acid (ABA) were found to be elevated, indicating an increased violaxanthin availability in VPZ plants. However, the increased basal ABA levels did not improve drought tolerance of VPZ transgenic potato plants under greenhouse conditions. The failure to benefit from improved photoprotection is most likely caused by a reduced radiation use efficiency under high light conditions resulting from a too strong NPQ induction. Mitigating this negative effect in the future might help to improve photosynthetic performance in VPZ expressing potato plants.
CRIS-Team Scopus Importer:2022-08-19
Keywords: drought; non-photochemical quenching; photosynthesis; potato; xanthophyll cycle